Simulator for signal analysis and digital communication systems - Li, Jingyi (Nanyang Technological University, 2021)
This report is concerned with the development of Graphical User Interface (GUI) regarding to Signal Analysis and Digital Communication Systems. The interfaces are constructed based on the fundamental concepts of signal and systems. The main covered topics are Fourier Transform, Filtering, Modulation and Demodulation. Before users interact with the interfaces, introductions are provided on the Main Page, illustrating the theories and concepts for Fourier Transform, Filtering and Modulation & Demodulation accordingly. It gives users a recap and brief overall picture for signal analysis before they move on to the next stage, GUI. Graphical User Interface is a dynamic graphical approach interacting with users. Three user-friendly GUIs are implemented using MATLAB, APP DESIGNER.The whole program including Welcome Page, Main page and 3 sub-interfaces can be consolidated into a standalone application or packaged under MATLAB. Graphical approaches give users an intuitive visualization on how the various operations on signals and systems are performed, which enable them to appreciate the knowledge easily, and have a better understanding on signal analysis.